Improved efficacy and in vivo cellular properties of human embryonic stem cell derivative in a preclinical model of bladder pain syndrome - Aram Kim (Nature Portfolio, 2017)
Abstract Interstitial cystitis/bladder pain syndrome (IC/BPS) is an intractable disease characterized by severe pelvic pain and urinary frequency. Mesenchymal stem cell (MSC) therapy is a promising approach to treat incurable IC/BPS. Here, we show greater therapeutic efficacy of human embryonic stem cell (hESC)-derived multipotent stem cells (M-MSCs) than adult bone-marrow (BM)-derived counterparts for treating IC/BPS and also monitor long-term safety and in vivo properties of transplanted M-MSCs in living animals. Controlled hESC differentiation and isolation procedures resulted in pure M-MSCs displaying typical MSC behavior. In a hydrochloric-acid instillation-induced IC/BPS animal model, a single local injection of M-MSCs ameliorated bladder symptoms of IC/BPS with superior efficacy compared to BM-derived MSCs in ameliorating bladder voiding function and histological injuries including urothelium denudation, mast-cell infiltration, tissue fibrosis, apoptosis, and visceral hypersensitivity. Little adverse outcomes such as abnormal growth, tumorigenesis, or immune-mediated transplant rejection were observed over 12-months post-injection. Intravital confocal fluorescence imaging tracked the persistence of the transplanted cells over 6-months in living animals. The infused M-MSCs differentiated into multiple cell types and gradually integrated into vascular-like structures. The present study provides the first evidence for improved therapeutic efficacy, long-term safety, and in vivo distribution and cellular properties of hESC derivatives in preclinical models of IC/BPS.